Rainfall Prediction In North Maharashtra Region Using Support Vector Machine - et. al., Husain H. Dawoodi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper a model using Support Vector Machine (SVM) for prediction of rainfall in the three districts of North Maharashtra Region has been proposed. Sixteen input metrological parameters such as temperature, wind speed, wind direction, humidity, visibility etc. were collected from 2009 to 2018 and one output parameter precipitation is used in this study. The model is validated using accuracy, precision, and recall. The results showed that SVM is capable to predict accurate results with 82% accuracy. The SVM model was found to be robust and efficient prediction model considering the varied geographical conditions of these three districts.